The Use of Instagram on Political Participation of Communication Students in Universitas Negeri Jakarta - Aisya Aisya; Ayu Priana; Salsabila Ardiningrum; Dini Safitri (Universitas Prof. Dr. Moestopo (Beragama), 2019)
Social media is now an important part of human life, not spared in the lives of teenagers. One of the social media that is now widely used by teenagers is Instagram. Along with the progress of various features provided, Instagram is now often used as a political campaign media. This study aims to determine the effect of using instagram on political participation in adolescents, especially students of the Communication Studies Program at the State University of Jakarta. This research uses the Uses and Gratification theory about media use and satisfaction. The benefit of cold research achieved in this study is to find out how to use Instagram to attract teenagers in political participation. In addition there are benefits to be achieved namely that the results of this study can be used for further similar studies. This study uses a quantitative approach. The unit of analysis of this research is the interest of adolescents in political participation. Data processing in this study uses simple linear regression analysis techniques. Based on the test results, the constant value and regression of the use of instagram variables of 0.278. Then the regression coefficient value of the political participation variable is 0.776. While the value of t arithmetic is 9,912 greater than the value of t table, which is 1.987. Based on this value, it is known that H0 is rejected and Ha is accepted. This means that there is an influence of the use of Instagram (X) on political participation (Y) of Communication Science students at Jakarta State University.